Aktivitas Antioksidan Likopen Buah Tomat (Solanum lycopersicum L.) Terblending dalam Minyak Padat Ikan Lele (Clarias sp): Antioxidant Activity of Lycopene from Tomato (Solanum lycopersicum L.) Blended Into Frying Fat from Catfish Oil (Clarias sp) - Eka Surya Wahyuningsih; Syamsuddin; Prismawiryanti; Dwi Juli Pusptasari (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2020)
Research on the antioxidant lycopene of tomato fruit (Solanum lycopersicum L.) blended in frying fat from catfish (Clarias sp) oil has been done. The purpose of this research is to determine the antioxidant activity of tomato lycopene before and after being grounded into frying fat and determine the quality of frying fat after being grounded with tomato lycopene. The antioxidant activity of tomato lycopene is determined by the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Analysis of frying fat quality includes determination of pH, determination of FFA (free fatty acid) levels, determination of total fat content, measurement of water content, peroxide number and organoleptic observation. Antioxidant activity of tomato lycopen was very high, namely with inhibition value of 89.79%; 90.34%; 91.49% and 92.10%. Frying fat analysis showed high antioxidant activity of lycopene tomatoes with 50.67% inhibition; 51.63%; 51.39% and 51.23%. The results of the analysis of the quality of frying fat are nearly same with SNI quality standards, except for peroxide numbers. Keywords: tomato, lycopene, antioxidants, frying fat, catfish, DPPH